"And the comrade faced the steel": Is 1948 Drama a Recruited Literature? - Caspi, Zahava (MiKAN, 2006)
This article attempts to examine from a new perspective the dramaticworks written during and immediately after the 1948 War ofIndependence, such as He Walked in the Fields and In the Plains ofthe Negev. I contend that the plays themselves do not in fact reflecttheir generally perceived image as representative of the normativeand consensual ideological stand of the Israeli collective at thattime. I further deconstruct the common viewpoint of the plays asaesthetically shallow, and reveal instead their poetic complexity.This new reading of the plays exposes the ambivalent stand of theirauthors towards the reality represented in them. Moreover, theirheroes are not exclusively the young Sabras, but also the generationof the founding fathers, who have been the main target of criticism.I suggest, for example, that the reflexive structure of a play-withina-play in He Walked in the Fields exposes an ideological innertension: while the outer play functions as a mythical text within theframework of the dominant Israeli ethos, the inner play subverts andironizes this idealization by revealing the falseness of the mythicperpetuation of its hero, Uri. Thus the play’s structure is shownto deepen and complicate its messages and enhance its aestheticcomplexity.